The first year experience - Higgins, Margaret (Kansas State University, 2010)
Students have many opportunities to familiarize themselves with their college after committing to a school. Institutions offer summer orientation and enrollment sessions, and many also offer extended orientation sessions that may include spending time in the residence halls or outdoor camps and activities. Upon arrival to campus, first year students are given a great deal of information about campus resources, culture and traditions. They may also have welcome week activities, first year seminar classes, learning communities, specialized housing accommodations,and a wealth of other opportunities to connect to the university. The purpose of this report is to explore both the unique challenges facing first year students and the varying support structures in place for them. To explore this topic, the unique needs facing first-year, residential students as it relates to student development and transition theories will be outlined. Focusing on institutional concerns, persistence will also be explored as a theoretical framework. Finally, to make this report relevant to Kansas State University, the first year programming efforts at twelve institutions will be synthesized and analyzed as a foundation for comparison. A proposal for potential programs at K-State will be presented.
Keywords: First-year students; First-year Programs; Orientation; Education, Higher (0745)